2014
DOI: 10.1016/j.diff.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized ECM effects on human mesenchymal stem cell stemness and differentiation

Abstract: Microenvironment extracellular matrices (ECMs) influence cell adhesion, proliferation and differentiation. The ECMs of different microenvironments have distinctive compositions and architectures. This investigation addresses effects ECMs deposited by a variety of cell types and decellularized with a cold-EDTA protocol have on multipotent human mesenchymal stromal/stem cell (hMSC) behavior and differentiation. The cold-EDTA protocol removes intact cells from ECM, with minimal ECM damage and contamination. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2016
2016
2107
2107

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 39 publications
(46 reference statements)
4
37
0
Order By: Relevance
“…Moreover, they have shown that MSCs cultured on osteogenic hMSC-or osteoblast-derived ECM are directed toward osteoblasts while MSCs on chondrocyte-or smooth muscle cell-derived ECM are induced into chondrocyte or smooth muscle cell, respectively. Rao et al have also shown that the osteoinductive potential of ECM produced by osteogenic hMSCs in early differentiation stage is greater than that in late differentiation stage, indicating that the ECM compositions at distinct differentiation stages are different [38].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, they have shown that MSCs cultured on osteogenic hMSC-or osteoblast-derived ECM are directed toward osteoblasts while MSCs on chondrocyte-or smooth muscle cell-derived ECM are induced into chondrocyte or smooth muscle cell, respectively. Rao et al have also shown that the osteoinductive potential of ECM produced by osteogenic hMSCs in early differentiation stage is greater than that in late differentiation stage, indicating that the ECM compositions at distinct differentiation stages are different [38].…”
Section: Discussionmentioning
confidence: 97%
“…*p < 0.05; **p < 0.01; n = 3. Scale bar: 200 μm [37,38]. Moreover, they have shown that MSCs cultured on osteogenic hMSC-or osteoblast-derived ECM are directed toward osteoblasts while MSCs on chondrocyte-or smooth muscle cell-derived ECM are induced into chondrocyte or smooth muscle cell, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…One possible reason could be lack of environmental signaling cues within the suboptimal two‐dimensional (2‐D) ex vivo culture milieu that compromises cellular responses and their differentiation potentials. Physiologically in vivo , MSCs reside in a three‐dimensional (3‐D) microenvironment surrounded by extracellular matrix (ECM) which is composed of a diverse and complex array of molecules that orchestrate cellular and molecular events during tissue development, repair, and remodeling . While various singular ECM components such as fibronectin, collagen, laminin, or the animal‐derived mixture matrigel have been employed as surface coatings to promote specific cellular biological functions, these commercially available products alone fail to replicate the compositional and structural complexity of natural‐occurring ECM and may provoke adverse host immunological responses due to the animal origins of some of these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically in vivo , MSCs reside in a three‐dimensional (3‐D) microenvironment surrounded by extracellular matrix (ECM) which is composed of a diverse and complex array of molecules that orchestrate cellular and molecular events during tissue development, repair, and remodeling . While various singular ECM components such as fibronectin, collagen, laminin, or the animal‐derived mixture matrigel have been employed as surface coatings to promote specific cellular biological functions, these commercially available products alone fail to replicate the compositional and structural complexity of natural‐occurring ECM and may provoke adverse host immunological responses due to the animal origins of some of these molecules. In contrasts, human‐derived ECM substrata, after removal of antigenic cellular components by decellularization could preserve the inherent ultrastructure and matrix components of native ECM including proteins, proteoglycans and glycosaminoglycans (GAG), thereby creating a more biomimetic microenvironment facilitating stem cell adhesion, migration and proliferation, whilst maintaining their potency in specific cell‐lineage differentiation …”
Section: Introductionmentioning
confidence: 99%
“…Native and in vitro cell culture derived ECMs are commonly used to produce scaffolds for tissue engineering (Almeida et al, 2014;Cunniffe et al, 2015;Jin et al, 2007;Kheir et al, 2011;Kim et al, 2015;Lau et al, 2012;Lu et al, 2011;Pati et al, 2015;Pattabhi et al, 2014;Sutherland et al, 2015); however, the ideal matrix to facilitate bone regeneration has yet to be established. As previously stated, the GP matrix contains many important growth factors for inducing bone growth which render it as an attractive option for generating an osteoinductive ECM derived scaffold.…”
Section: Introductionmentioning
confidence: 99%